PENGARUH PENDEKATAN RME TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI OPERASI HITUNG PECAHAN KELAS V SD - Bella Risa Alfianda1; Mislinawati; Linda Vitoria (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of critical thinking skills is an important aspect of mathematics learning in elementary schools, particularly in helping students understand concepts logically and systematically. However, in practice, mathematics learning is still predominantly teacher-centered, resulting in limited student involvement and underdeveloped critical thinking skills, especially in fraction arithmetic operations. Therefore, a learning approach that connects mathematical concepts to real-life contexts is needed to make learning more meaningful. One approach that can be applied is Realistic Mathematics Education (RME). This study aims to determine the effect of the Realistic Mathematics Education (RME) approach on students’ critical thinking skills in fraction arithmetic operations for fifth-grade students at SD Negeri 1 Pagar Air, Aceh Besar Regency. This study employed a quantitative approach using a quasi-experimental research design with the Nonequivalent Control Group Design. The sample consisted of two classes: class VA as the experimental group, which applied the RME approach, and class VB as the control group, which used conventional learning methods. Data were collected through critical thinking skill tests in the form of essay questions administered during the pretest and posttest stages. The data were analyzed using N-Gain analysis, normality tests, and hypothesis testing. The results showed that the Asymp. Sig. (2-tailed) value was 0.003 < 0.05, therefore, it can be concluded that the application of the Realistic Mathematics Education (RME) approach has a significant effect on students’ critical thinking skills in fraction arithmetic operations for fifth-grade students at SD Negeri 1 Pagar Air, Aceh Besar Regency.